Performance management in the voluntary sector – responding to complexity. (24th November 2017) - Lowe, Toby
Abstract : This paper reviews the rise of new public management approaches to performance management in the voluntary sector and argues that outcome-based performance management – the dominant paradigm for performance management in the sector – fails to respond to the complex nature of voluntary sector challenges and activity. The paper argues that we need a new paradigm for performance management, which focuses on learning and improvement of practice, not on accountability for outcomes.